(untitled) (Hematology Meeting Reports, 2009)
The RICOVER60 trial has shown that 6 cycles of CHOP-14 with 8 applications of rituximab (6xR-CHOP-14) was superior to 8xR-CHOP-14, 6xCHOP-14 and 8xCHOP-14 in elderly patients with CD20-positive aggressive lymphoma. In that trial 117/306 (36%) of the patients in the 6xRCHOP- 14 arm were assigned to receive additional radiotherapy (Rx) to bulky disease (Pfreundschuh et al., Lancet Oncol 2008). To study the relevance of additional Rx to bulky disease we subsequently initiated a prospective study in which no Rx was planned after 6 x R-CHOP-14.